PLASMA EXPRESSION OF VASCULAR ENDOTHELIAL GROWTH FACTOR (VEGF) AND BASIC FIBROBLAST GROWTH FACTOR (bFGF) IN PATIENTS WITH BRAIN TUMORS. - Deyan Handzhiev; Georgi Kiuchukov; Yavor Enchev; Toni Avramov; Radoslav Georgiev; Stanislava Varbanova (Journal of IMAB, 2015)
OBJECTIVE: Angiogenesis and angiogenic growth factors are of basic importance in the development and progresion of brain tumours. The purpose of the study was to evaluate the plasma levels of two angiogenic factors Vascular Endothelial Growth Factor (VEGF) and Basic Fibro blast Growth Factor (bFGF) inpatients with brain tumors and potential possibilities to use them with predictive value. MATERIAL – METHOD: In order to determine amount of VEGF and FGFb in plasma were examined 35 patients, (glioblastoma multiforme, GBM, n=7; astrocytoma, n=7; meningioma, n=11; and healthy control group, n=10) were analysed. For determination of plasma concentrations of angiogenic factor, highly specific enzyme-linked immuno sorbent assays (ELISAs) were used. The data underwent regression and correlation analysis for estimation of the eventual interrelations. RESULTS: Median levels of bFGF in glioblastoma patients were higher compared with those with low grade gliomas, meningiomas or healthy patients. Highest levels of VEGF concentrations were detected in plasma derived from patients suffering from LGG. Plasma expression of these angiogenic factors shows dynamic changes pre- and postoperative, but cannot be explained only with tumor resection, grade or type of the tumor, and probably is result of physiological regeneration of the operative wound. No correlation between the survival time of the patients and the plasma levels of the tested growth factors was obtained. CONCLUSIONS: Expression of VEGF and bFGF in plasma are not reliable marker. The detectability of the angiogenic factors VEGF and bFGF in the plasma of patients suffering from various types of brain tumours is described. The plasma detectability of the individual angiopoietic factors seems to depend at least partly on the tumour type as well as on tumour progression. This might be of prognostic and therapeutic relevance.